Zinc oxide bulk, thin films and nanostructures : processing, properties and applications - Jagadish, C. (Chennupati); Pearton, S. J. (Amsterdam ; Boston : Elsevier, 2006)
Zinc oxide is a direct, wide bandgap semiconductor material with many promising properties for blue/UV optoelectronics, transparent electronics, spintronic devices and sensor applications. ZnO has been commonly used in its polycrystalline form for over a hundred years in a wide range of applications: facial powders, ointments, sunscreens, catalysts, lubricant additives, paint pigmentation, piezoelectric transducers, varistors, and as transparent conducting electrodes . Its research interest has waxed and waned as new prospective applications revive interest in the material, but the applications have been limited by the technology available at the time. ZnO can be grown on inexpensive substrate, such as glass, at relatively low temperatures. Nanostructures, such as nanowires and nanorods, have been demonstrated. These structures are ideal for detection applications due to its large surface area to volume ratio. Recent improvements in the growth of high quality, single crystalline ZnO in both bulk and epitaxial forms has renewed interest in this material. Significant efforts in the last few years have been aimed at controlling conductivity and improving crystal quality. However, in order to fully realize ZnO devices, additional material and process development issues must be overcome. The purpose of this book is to provide an overview of recent progress in ZnO research and identify future areas that need work.An in-depth exploration of the broad uses of zinc oxide within the fields of materials science and engineering.With an in-depth exploration of the following topics, this book covers the broad uses of zinc oxide within the fields of materials science and engineering: - Recent advances in bulk , thin film and nanowire growth of ZnO (including MBE, MOCVD and PLD)
- The characterization of the resulting material (including the related ternary systems ZgMgO and ZnCdO), - Improvements in device processing modules (including ion implantation for doping and isolation ,Ohmic and Schottky contacts , wet and dry etching), - The role of impurities and defects on materials properties - Applications of ZnO in UV light emitters/detectors, gas, biological and chemical-sensing, transparent electronics, spintronics and thin filmForeword 1. Basic Properties and Applications of ZnO (V.A. Coleman and C. Jagadish) 2. Doping and Defects in ZnO (D.C. Look) 3. Synthesis and Characterization of Nitrogen-Doped ZnO Films Grown by MOCVD (T.J. Coutts, Xiaonan Li, T. Barnes, B. Keyes, C.L. Perkins, S.E. Asher
Shengbai Zhang, Su-Huai Wei and S. Limpijumnong) 4. Pulsed Laser Deposition of ZnO (V. Gupta and K. Sreenivas) 5. Optical Properties of ZnO and Related Alloys (U. Ozgur and H. Morkoc) 6. Minority Carrier Transport in ZnO and Related Materials (O. Lopatiuk, A. Osinsky and L. Chernyak) 7. Contacts to ZnO (Jae-Hong Lim and Seong-Ju Park) 8. Ion Implantation into ZnO (S.O. Kucheyev and C. Jagadish) 9. Advances in Processing of ZnO (K. Ip, S.J. Pearton, D.P. Norton and F. Ren) 10. Novel Nanostructures and Nanodevices of ZnO (Zhong Lin Wang) 11. ZnO/ZnMgO heterojunction FETs (M. Yano, K. Koike, S. Sasa and M. Inoue) 12.ZnO Thin Film Transistors (R. Hoffman) 13. ZnO Piezoelectric Devices (Yicheng Lu, N. Emanetoglu and Ying Chen) 14. Gas, Chemical and Biological Sensing with ZnO (Young-Woo Heo, F. Ren and D.P. Norton) 15. ZnO-Based Light Emitters (A. Osinsky and S. Karpov) 16. Ferromagnetism in ZnO Doped With Transition Metal Ions (D.P. Norton, S.J. Pearton, J.M. Zavada, W.M. Chen and I.A. Bouyanova) (more)
With an in-depth exploration of the following topics, this book covers the broad uses of zinc oxide within the fields of materials science and engineering: - Recent advances in bulk , thin film and nanowire growth of ZnO (including MBE, MOCVD and PLD), - The characterization More... of the resulting material (including the related ternary systems ZgMgO and ZnCdO), - Improvements in device processing modules (including ion implantation for doping and isolation ,Ohmic and Schottky contacts , wet and dry etching), - The role of impurities and defects on materials properties - Applications of ZnO in UV light emitters/detectors, gas, biological and chemical-sensing, transparent electronics, spintronics and thin film
Basic Properties and Applications of ZnO -- Doping and Defects in ZnO -- Synthesis and Characterization of Nitrogen-Doped ZnO Films Grown by MOCVD -- Pulsed Laser Deposition of Zinc Oxide (ZnO) -- Optical Properties of ZnO and Related Alloys -- Minority Carrier Transport in ZnO and Related Materials -- Contacts to ZnO -- Ion Implantation into ZnO -- Advances in Processing of ZnO -- Novel Nanostructures and Nanodevices of ZnO -- ZnO/ZnMgO Heterojunction FETs -- ZnO Thin-Film Transistors -- ZnO Piezoelectric Devices -- Gas, Chemical and Biological Sensing with ZnO -- ZnO-Based Light Emitters -- Ferromagnetism in ZnO Doped with Transition Metal Ions -- Index
Includes bibliographical references and index.
1
Keywords: Zinc oxide; Zinc oxide thin films; Semiconductors; Nanostructured materials; SCIENCE - Chemistry - General; SCIENCE - Nanostructures; TECHNOLOGY - Material Science